Abrasive wear behavior of austempered ductile iron with niobium additions - Souza Oliveira Pimentel A.* (2019)
© 2019 Elsevier B.V.Carbidic Austempered Ductile Iron (CADI) microstructures containing eutectic carbides can be produced by the addition of carbide stabilizing elements, such as chromium. Carbides formed from the addition of Cr are eutectic of M3C type. The presence of such hard phases can enhance the abrasion wear resistance of ductile iron. A new CADI can be produced by the addition of Nb. Niobium carbide particles are formed in the beginning of solidification and remain stable once they are insoluble in solid iron matrix. The dry sand abrasive wear resistance of ductile irons alloyed with 1.0, 1.8, and 2.4 wt% Nb were tested in both “as-cast” and “heat treated” conditions using standard ASTM G65. Results were compared to abrasive wear data obtained on ductile iron alloyed with 1 wt% Cr, CADI (1 wt% Cr), and the basic composition of iron without carbide stabilizing elements. In the “as-cast” condition, the addition of Nb did not lead to a reduction in wear, while CADI with Nb is a promising substitute for CADI with Cr addition, because both materials showed very similar values of abrasion resistance. Micro-ploughing and micro-cutting mechanisms were observed on the worn surfaces of ductile irons. Abrasive wear resistance of these alloys was correlated with the volume fraction of carbides.